Activation of the brain melanocortin system is required for leptin‐induced modulation of chemorespiratory function. (30th September 2014) - Bassi, M.; Nakamura, N. B.; Furuya, W. I.; Colombari, D. S. A.; Menani, J. V.; do Carmo, J. M.; da Silva, A. A.; Hall, J. E.; Colombari, E.
Abstract Melanocortin receptors (MC3/4R) mediate most of the metabolic and cardiovascular actions of leptin. Aim Here, we tested if MC4R also contributes to leptin's effects on respiratory function. Methods After control measurements, male Holtzman rats received daily microinjections of leptin, SHU9119 (MC3/4R antagonist) or SHU9119 combined with leptin infused into the brain lateral ventricle for 7 days. On the 6th day of treatment, tidal volume (VT), respiratory frequency (fR) and pulmonary ventilation (VE) were measured by whole‐body plethysmography during normocapnia or hypercapnia (7% CO2). Baseline mean arterial pressure (MAP), heart rate (HR) and metabolic rate were also measured. VE, VT and fR were also measured in mice with leptin receptor deletion in the entire central nervous system (LepR/Nestin‐cre) or only in proopiomelanocortin neurones (LepR/POMC‐cre) and in MC4R knockout (MC4R−/−) and wild‐type mice. Results Leptin (5 μg day−1) reduced body weight (~17%) and increased ventilatory response to hypercapnia, whereas SHU9119 (0.6 nmol day−1) increased body weight (~18%) and reduced ventilatory responses compared with control‐PBS group (Lep: 2119 ± 90 mL min−1 kg−1 and SHU9119: 997 ± 67 mL min−1 kg−1, vs. PBS: 1379 ± 91 mL min−1 kg−1). MAP increased after leptin treatment (130 ± 2 mmHg) compared to PBS (106 ± 3 mmHg) or SHU9119 alone (109 ± 3 mmHg). SHU9119 prevented the effects of leptin on body weight, MAP (102 ± 3 mmHg) and ventilatory response to hypercapnia (1391 ± 137 mL min−1 kg−1). The ventilatory response to hypercapnia was attenuated in the LepR/Nestin‐cre, LepR/POMC‐cre and MC4R−/− mice. Conclusion These results suggest that central MC4R mediate the effects of leptin on respiratory response to hypercapnia.